Periódicos científicos de acesso aberto do Brasil e da Espanha: modelo terminológico e padrão das equipes editoriais e científicas e da avaliação por pares - Edna da Silva Angelo (2022)
The journal is the main channel for sharing research results. The objective of this study is to analyze the characteristics, editorial teams and peer review of Brazilian and Spanish open access scientific journals, in order to formalize a terminological and standard model for these publications. The theme is justified by the scarcity of studies in the field of Information Science and the need to know the publication system of journals. This is a descriptive, exploratory and mixed approach research, whose analysis corpus brought together scientific, open access and Brazilian and Spanish journals. As for the technical procedures, a documental research was carried out, extracting data from the Directory of Open Access scholarly Resources; Directory of Open Access Journals; Regional Information System on Line for scientific journals from Latin America, the Caribbean, Spain and Portugal; Dulcinea Portal; Brazilian Network of Digital Preservation Services; Catalan Magazines es Amb Acces Obert; publishers' and journals' websites; and reports from editors. Data were collected using a registration form and virtual meetings were held via Google Meet and individually, with the participation of editors and researchers linked to the area of Communication and Information. From the results, it was found that there were 5,848 journals, most of them established in the period from 2010 to 2014, of which 1,601 were discontinued and, of those in force, 2,628 are Brazilian, 1,619 are Spanish and the regions with the highest Gross Domestic Product concentrate the largest number of publications. As for editorial characteristics, Education and History represent the most recurrent subjects in both countries; 88% of Brazilian and 65% of Spanish journals use the OJS platform; Spain has a greater number of editions available per title (48), while Brazil has, on average, 35 editions; in Spain, 38% of journals are published annually, while in Brazil, most (43%) publish twice a year. With regard to the scientific team, in both countries, the analyzes found that the editorial responsibility lies with educational institutions and associations and most of the scientific team in both countries is composed of 20 to 29 people; the two countries use a variety of nomenclatures to designate editorial teams, with 713 being located in Brazil and 623 in Spain, whose attributions of these teams are performed by the editor-in-chief in 58% of Brazilian journals and in 42% of Spanish; it was noticed that 60% of Brazilian and 32% of Spanish journals describe the technical team, with 819 expressions for this team in Brazilian journals and 297 in Spanish. With regard to peer evaluation, the blind evaluation system predominates, whose evaluation process is composed of three phases: pre-evaluation, evaluation and reviews, and the practice of inviting external evaluators is not very common in both countries. In short, because of the terminological variety of the teams involved in management, the proposed model associated terms, establishing a standardized terminology set, with the purpose of preventing terms from being established for convenience, without selective criteria. The model allowed efficient indexing and was evaluated as adequate to meet the informational needs of scientific editors.